2020
DOI: 10.3390/cancers12051163
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG Pet Parameters and Radiomics Features Analysis in Advanced Nsclc Treated with Immunotherapy as Predictors of Therapy Response and Survival

Abstract: Objectives: (1.1) to evaluate the association between baseline 18F-FDG PET/CT semi-quantitative parameters of the primary lesion with progression free survival (PFS), overall survival (OS) and response to immunotherapy, in advanced non-small cell lung carcinoma (NSCLC) patients eligible for immunotherapy; (1.2) to evaluate the application of radiomics analysis of the primary lesion to identify features predictive of response to immunotherapy; (1.3) to evaluate if tumor burden assessed by 18F-FDG PET/CT (N and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
80
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(87 citation statements)
references
References 32 publications
3
80
2
2
Order By: Relevance
“…Polverari et al . observed significant differences in tumour heterogeneity (as defined by kurtosis and skewness) between patients with progressive disease (PD) and non-PD 21 , while the study by Mu et al . proposed a combined PET and CT radiomics signature for predicting patient PFS and OS.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Polverari et al . observed significant differences in tumour heterogeneity (as defined by kurtosis and skewness) between patients with progressive disease (PD) and non-PD 21 , while the study by Mu et al . proposed a combined PET and CT radiomics signature for predicting patient PFS and OS.…”
Section: Introductionmentioning
confidence: 94%
“…On the other hand, few immunotherapy clinical studies examined possible non-invasive imaging biomarkers, but there is still a lack of research performed in NSCLC patients. 14 Three retrospective anti-PD-1 studies showed associations of pre-treatment sum of maximum standardized uptake values (SUV max ) of all lesions (SUV maxwb ) 19 , SUV max of the most avid lesion 20 , and volumetric parameters (metabolic tumour volume [MTV], and total lesion glycolysis [TLG]) 21 , with NSCLC patient response as defined by RECIST. However, significant correlations of these features with OS were not observed.…”
Section: Introductionmentioning
confidence: 99%
“…In advanced non-smallcell lung carcinoma, patients with higher values of MTV and TLG had higher probability of disease progression compared to those patients presenting with lower values, while SUV max did not show a correlation with progressive disease (PD) status. MTV also resulted in being significantly different among partial response (PR), stable disease (SD), and PD groups, while SUV max was confirmed to not be associated with response to therapy (25). Besides, some papers have correlated metabolic parameters derived from the baseline PET to metabolic therapy response.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 shows a summary of the topics and the papers included for each topic [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. The majority of papers are focused on prostate cancer (PCa) and radiomics.…”
mentioning
confidence: 99%
“…Indeed, radiomics can be used as a tool for the prediction of outcomes in terms of response to therapy or prognosis in patients undergoing immune check point inhibitors, as stated by Polverari et al [ 29 ]. The use of imaging as a predictive biomarker of response to immunotherapy has been discussed by some authors [ 5 , 6 , 7 ], in the present issue.…”
mentioning
confidence: 99%